1998
DOI: 10.1126/science.282.5386.95
|View full text |Cite
|
Sign up to set email alerts
|

Solution Properties of Single-Walled Carbon Nanotubes

Abstract: Naked metallic and semiconducting single-walled carbon nanotubes (SWNTs) were dissolved in organic solutions by derivatization with thionychloride and octadecylamine. Both ionic (charge transfer) and covalent solution-phase chemistry with concomitant modulation of the SWNT band structure were demonstrated. Solution-phase near-infrared spectroscopy was used to study the effects of chemical modifications on the band gaps of the SWNTs. Reaction of soluble SWNTs with dichlorocarbene led to functionalization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
1,577
2
15

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,531 publications
(1,667 citation statements)
references
References 16 publications
46
1,577
2
15
Order By: Relevance
“…29 Electronic transitions between the energy bands of SWNTs ( Figure 2) can be observed by standard spectroscopic techniques. 7,27,30 Besides the heterogeneity of the samples with respect to the tube diameters and helicities, impurity doping contributes to the breadth of the absorption features. 27 Since the band gaps are inversely proportional to the tube diameters, structural information can be derived from the band transition energies.…”
Section: Preparation and Solid State Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…29 Electronic transitions between the energy bands of SWNTs ( Figure 2) can be observed by standard spectroscopic techniques. 7,27,30 Besides the heterogeneity of the samples with respect to the tube diameters and helicities, impurity doping contributes to the breadth of the absorption features. 27 Since the band gaps are inversely proportional to the tube diameters, structural information can be derived from the band transition energies.…”
Section: Preparation and Solid State Propertiesmentioning
confidence: 99%
“…106,107 Electronic spectroscopy showed that the band-gap transitions in the semiconducting tubes were completely disrupted at a functionalization level of 2% of the available SWNT carbon atoms. 7 Apart from the carbene chemistry, 6 97 While the side walls of the carbon nanotubes were once considered impregnable (like the fullerenes), 32,33 there is now an extensive chemistry, 7,93,94,96,97,110 and these initial studies suggest that the chemistry of the carbon nanotubes will ultimately rival that of the carbon fullerenes.…”
Section: Covalent Chemistry Of the Walls Of The Carbon Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting CNTs that are obtained typically display lengths ranging from 100 to 300 nm, with both ends and the sidewalls decorated predominantly with a high density of carboxyl groups. In an alternative oxidation protocol (Subheading 3.3.2), nanotube shortening can be minimized by refluxing the CNTs in concentrated nitric acid alone (33). Using this approach, the resulting CNTs have most of their pristine mechanical and electrical properties preserved; however, oxidation only occurs at the opening of the tube caps and carboxylic acid functional groups are only formed at defect sites found along the sidewalls.…”
Section: Add 5 Mg Of Capped Magnetic Iron Oxide Nanoparticles (Obtainmentioning
confidence: 99%